2008
DOI: 10.1088/0954-3899/36/1/015107
|View full text |Cite
|
Sign up to set email alerts
|

Alpha decay, cluster decay and spontaneous fission in294–326122 isotopes

Abstract: The cluster decay half lives for 122 isotopes are computed for various clusters ranging from an alpha particle to 70 Ni within the Coulomb and proximity potential model. The computed alpha decay half lives agree with the values calculated using the Viola-Seaborg-Sobiczewski (VSS) systematic formulas. The half lives for spontaneous fission of these isotopes are carried out using the formula of Ren et al. It is found that the alpha emission is the dominant mode of decay for isotopes with mass number A < 306, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…So through our study, we could confidently predict the new island for the cluster radioactivity leading to the residual superheavy isotope 298 114 and its neighbors. We would like to mention that, the results obtained through our study closely agree with that of the early predictions [36][37][38][39][40]. Thus we have established the fact that, the isotope 298 114 should be considered as the next predicted spherical doubly magic nucleus after the experimentally observed doubly magic nuclei 208 Pb and 100 Sn.…”
Section: Semi-empirical Relation Of Santhosh Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…So through our study, we could confidently predict the new island for the cluster radioactivity leading to the residual superheavy isotope 298 114 and its neighbors. We would like to mention that, the results obtained through our study closely agree with that of the early predictions [36][37][38][39][40]. Thus we have established the fact that, the isotope 298 114 should be considered as the next predicted spherical doubly magic nucleus after the experimentally observed doubly magic nuclei 208 Pb and 100 Sn.…”
Section: Semi-empirical Relation Of Santhosh Et Alsupporting
confidence: 88%
“…Within the preformed cluster model, Gupta et al, [38] have calculated the alpha half-life time value of 285 114, indicating that the isotope is stable against α decay and the magicity of protons at Z = 114 or of neutrons at N ≈ 172 was accounted for this stability. Alpha decay studies on Z = 122 [39] and cluster decay studies based on the concept of cold valley in fission and fusion on Z = 116 [40] by Santhosh et al, also indicate neutron shell closure at N = 162, 184 and proton shell closure at Z = 114 and have shown that 298 114…”
Section: Introductionmentioning
confidence: 96%
“…Our observations and calculations strongly support the possibility of neutron magic numbers N=184, 200. We can also identify that proton shell closure occurs at Z=120 in the super heavy region which have already pointed out in [87] and hence 184 304 120 and 200 320 120 are doubly magic nuclei. From our observation N=212 can be a neutron magic number, so 212 332 120 is also be a doubly magic nucleus.…”
Section: Resultssupporting
confidence: 73%
“…This indicates that shell effects play a key role to select possible cluster emissions and the study of cluster emission can be used to identify shell effects including the very weak sub-shell closures [3][4][5]. Several theoretical approaches can be employed to investigate cluster emission: among them the preformed cluster model (PCM) [3,5,6], in which the cluster is assumed to be preformed in the parent nucleus and the preformation factor for all possible clusters is calculated by solving the Schrödinger equation for the dynamical flow of mass and charge; the super-asymmetric fission model [7][8][9][10][11], which is based on the Gamow's idea of barrier penetration; the unified fission model [12][13][14](some authors name it the Coulomb and proximity potential model); a cluster model with a mean-field cluster potential can also provide a good description of cluster emission [15].…”
mentioning
confidence: 99%